Evaluation of Results of Anterior Cervical Discectomy Fusion (ACDF) by Cervical Cage with Bone Graft for the Treatment of Single Level Cervical Spondylotic Myelopathy - Chowdhury, R; Mishra, D; Batajoo, S; Shrestha, M (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Cervical spondylotic myelopathy (CSM) is a common spinal cord disorder that develops in elderly people. Anterior cervical decompression and fusion (ACDF) is an effective and reliable procedure for the treatment of CSM.Objective: To find out the results of ACDF by cervical cage with bone graft for the treatment of single level cervical spondylotic myelopathy.Methods: This prospective observational study was conducted in the Department of Orthopedics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, over a period of two years from March 2015 to August 2017. Forty patients with cervical spondylotic myelopathy were diagnosed on the basis of presenting complains, clinical examination and investigations and were enrolled in this study. The history of the patients was collected, clinical examination was done and relevant investigations were done for each patient. In this study, Nurick grading and VAS scale were used for evaluation of the result.Result: Male gender was predominant in this study; male-female ratio was 2.63:1. Mean age of the patients was 45.9 ± 9.1 years within the range of 30-65 years. Both sides were affected in 14 (35.0%) cases, only right side was affected in 15 (37.5%) cases and only left side was affected in 11 (27.5%) cases. Involved disc spaces were C3/4 (10.0%), C4/5 (22.5%), C5/6 (42.5%) and C6/7 (25.0%). Transientdysphagia was observed in 2 (5.0%), transient para paresis in 1 (2.5.0%), wound infection in 1(2.5.0%) case and damage to the dura was observed in 1 (2.5.0%) case. Signs of fusion were observed in 10 (25.0%) cases after 3 months, 30 (75.0%) cases after 6 months and in all patients after 12months. The result was found to be excellent in 35 (87.5%) and good in 5 (12.5%) cases.Conclusion: Anterior cervical discectomy and fusion by cervical cage with bone graft is an effective procedure for management of CSM.